UJI ANTIOKSIDAN FORMULASI SEDIAAN GRANUL EFFERVESCENT EKTRAK BUAH BELIMBING WULUH (Averrhoa bilimbi L.) DENGAN VARIASI KONSENTRASI ASAM DAN BASA - amaliya, riski (LPPM Akafarma Sunan Giri Ponorogo, 2024)
Star fruit (Averrhoa bilimbi L) has antioxidant activity like its leaves. The formulation of star fruit in effervescent granule preparations is one of the attractive instant drinks to make it easier for people in Indonesia to consume star fruit. The purpose of this study was to determine the antioxidant activity of star fruit ethanol extract, effervescent granules of star fruit ethanol extract using the ABTS method (2,2-Azinobis 3- Ethylbenzothiazoline 6-Sulfonic Acid) and to determine the effect of variations in acid and base concentrations on the physical quality of effervescent granule preparations. Star fruit extract is obtained by maceration using a 96% ethanol solvent. This research method is an experimental research method. Starfruit effervescent granules are made with a ratio of citric acid, tratatic acid, and sodium bicarbonate consisting of formula 1 (26%:13%:32.5%), formula 2 (13%:26%:32.5%), and formula 3 (20%:10%:35.2%). The results showed that the IC50 value of ethanol extract was 26.168 μg/ml, effervescent granules had an IC50 value of 38.714 μg/ml, including having very strong antioxidant activity. The physical quality evaluation test of effervescent granules obtained optimal results, namely formulation 2, because it met all requirements.